FORMULASI, EVALUASI DAN UJI ANTIBAKTERI SEDIAAN GEL EKSTRAK ETANOL DUAN JAMBU BIJI (Psidium guajava L.) SEBAGAI ANTI JERAWAT - Nurfitriyana Nurfitriyana; Rini Yanuarti; Indri Dyah Pangesti (Institut Sains dan Teknologi Al-Kamal, 2021)
Acne is skin problems that can be overcome by using herbal plants, one of which is guava leaves. Guava leaves (Psidium guajava L.) contains tannins, saponins, polyphenols and flavonoids that can inhibit the growth of acne-causing bacteria. This study aims to formulate guava leaf extract (Psidium guajava L.) and evaluate the results of antibacterial tests on gel preparations as anti-acne. The ethanol extract was extracted and formulated using Na-CMC. Evaluation of the antibacterial activity of guava leaf extracts and preparations using Staphylococcus aureus and Eschericia coli bacteria. The results showed that the ethanol extract of guava leaves (Psidium guajava L.) with a concentration of 15% had antibacterial activity against Staphylococcus aureus with an inhibition area of ​​6.75 cm, and the gel preparation of guava leaf ethanol extract (Psidium guajava L.) resistance 0.2 mm. The evaluation found that the gel preparation of ethanol extract of guava leaves (Psidium guajava L.) can be used as an anti-acne gel.